Selective synthesis of tricyclopentadiene from dicyclopentadiene with homogeneous Pd catalysts. (20th January 2014) - Woo, Jeong Oh; Park, Jong‐Eun; Han, JeongSik; Kwon, Tae Soo; Kim, Yeong‐Joon; Son, Kyung‐sun
<x xml:space="preserve">Abstract</x> We explored a simple synthetic strategy with homogeneous palladium catalysts to afford a [2 + 2] isomer of tricyclopentadiene in good yield (up to 98% from cyclopentadiene and up to 78% from dicyclopentadiene) with high selectivity. The effects of a variety of palladium precursors, phosphorus ligands and acids were investigated to improve the productivity and selectivity of the tricyclopentadiene synthesis. The reaction conditions were evaluated and their effects on the product distribution were also discussed. Copyright © 2014 John Wiley & Sons, Ltd.